Comparison of IPv6 transition mechanism / Noor Hafiza Abd Rahman - Abd Rahman, Noor Hafiza
Exhaustion of the current version of IPv4 led to the new alternative which is by migrating IPv4 to a new protocol, IPv6. The migration to IPv6 will be facilitated with several transition mechanisms. Even though every process requires compliances with corresponding capabilities, all transition mechanisms have a similar objective which is to ensure smooth transition. This paper focuses on the performance comparison of IPv6 transition namely dual stack and 6to4 tunneling. The evaluations are based on test bed setup where IPv6 transition mechanisms of data transmission were tested. The network performance application software has been applied to end-to-end devices to obtain the throughput and round trip time for TCP and UDP on the transport layer. The performance of IPv6 was compared with the native IPv4 environment. The results proved that dual stack IPv6 transition mechanism is a more preferable method in the case of TCP data transmission.